New occurrence of corn and rice strains of Spodoptera frugiperda (Lepidoptera: Noctuidae) in Bali and Lesser Sunda: Genetic diversity, distribution, and damage - I KADEK WISMA YUDHA; I WAYAN SUPARTHA; I WAYAN SUSILA; PUTU SUDIARTA; I NYOMAN WIJAYA; PUTU ANGGA WIRADANA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yudha IKW, Supartha IW, Susila IW, Sudiarta P, Wijaya IN, Wiradana PA. 2024. New occurrence of corn and rice strains of Spodoptera frugiperda (Lepidoptera: Noctuidae) in Bali and Lesser Sunda (Indonesia): Genetic diversity, distribution, and damage. Biodiversitas 25: 1890-1900. Spodoptera frugiperda is an invasive pest with rapid proliferation and is responsible for reducing corn productivity in several regions in Indonesia, including Bali and Lesser Sunda in Indonesia. Therefore, this study aimed to determine the geographic distribution, genetic diversity, and specific genes of S. frugiperda as well as assess its attacks in Bali and Lesser Sunda (NTB and NTT) regions. The study procedures were carried out using field surveys, followed by molecular identification to determine the genetic diversity of S. frugiperda with the COI locus. A total of 150 infected corn plants were sampled using the diagonal sampling method, with a unit size of 5 m × 5 m. The distribution data obtained were then analyzed using the QGIS application and SPSS 22 for statistical analysis. The geographic distribution results showed that S. frugiperda was evenly distributed in the provinces of Bali and Lesser Sunda, with the observation of 2 strains, namely corn and rice. Corn strain was more specifically found in the Karangasem, Flores, Lombok Highlands, and Timor areas, while rice strain occured in the Jembrana, Sumbawa, Sumba, Flores, and Lombok lowland areas. In addition, a total of 12 specific nucleotide bases from S. frugiperda gene were found in Bali, NTB, and NTT regions. The findings also showed that the haplotype network of Bali, NTB, and NTT populations was effectively isolated from other locations and was in the process of genetic divergence. The 3-year invasion of S. frugiperda in Indonesian territory was reported to have experienced a process of genetic population development. Lombok Island had the highest average plant damage at 54.63%, which was not significantly different from the value of Sumbawa, Bali, and Sumba at 47.79%, 42.65%, and 40.72%, respectively. On the other hand, the lowest plant damage level in Timor at 20.95%, followed by Flores (at 30.38%).